A Voz do Oeste e sua relação com as articulações burguesas e o estado em Toledo (1964 1970) - Souza, Ivanor Mann de (2010)
In order to problematize the State acting in Toledo, it is taken as base an initial discussion about its origin and its integration into the civil society; it intends to identify the State into the social relationships, going beyond the simple presentation defended by the theoretical liberalists. This research, based on the historical materialism, especially in the gramscian conception of State, aims to understand the civil society of Toledo and the relationships that it establishes in the State configuration with the municipality, which is disputed by the bourgeoisie in the class struggle, in order to defend their interests. This research discuss about the State in Toledo, taking as base literature sources, bills approved by City Council, archives from the Historical Museum of Toledo and it is, essentially, based on the analyses of A Voz do Oeste newspaper trajectory, discussing how it became a private apparatus from the hegemony of some of the local bourgeoisie in order to perform their project within the municipal administration. To clarify how the newspaper was used to defend the interests of its represents, it is noticed its relationship with the two municipal managements of the mayors Avelino Campagnolo (1964-1969) and Egon Pudell (1969-1970), until the year the journal is extinct. By the fact the two mayors managed the city one after the other, it is possible to understand the posture of the newspaper regarding the two municipal governments. Although both mayors defended the bourgeoisie groups, it is possible to realize that even though the bourgeoisie, in the class struggle, is involved cohesively and unified with the objective of the maintenance of the exploitation of the working class, the different fractions that constitute the bourgeoisie have cracks and these can be notice on how the newspaper dealt with the two administrations and in its intervention in the campaign for the mayor electoral dispute in Toledo in 1968, when burghers groups, that expressed themselves through the newspaper, acted effectively to achieve their goals. Therefore, this work builds up a discussion on the organizational forms constituted by these groups, in particular through the establishment and maintenance of the A Voz do Oeste newspaper, aiming its hegemony statement